PENGGUNAAN MODEL PEMBELAJARAN BERBASIS SAVI TERHADAP PEMAHAMAN BELAJAR GEOGRAFI PESERTA DIDIK FASE E SMAN 1 LINGGO SARI BAGATI - Yolanda Yunita Sari; Slamet Rianto; Loli Setriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by students' low understanding of geography, particularly the lithosphere. This is due to the continued dominance of conventional learning methods that do not actively involve students in the learning process. Students tend to be passive and struggle to understand the material because the learning does not align with their learning styles. This research used a quantitative method with a quasi-experimental design. The population in this study were students in phase E at SMAN 1 Linggo Sari Baganti in the 2024-2025 academic year, consisting of 10 phases with a total of 354 students. The sample in this study was phase E1 as the experimental phase and phase E4 as the control phase. Based on the t-test results obtained, the significance value was 0.025 <0.05, meaning Ha was accepted and H0 was rejected. Thus, it can be concluded that the use of the SAVI-based learning model has a significant effect on the understanding of geography learning among students in phase E at SMAN 1 Linggo Sari Baganti.